Dienophile‐Modified Mannosamine Derivatives for Metabolic Labeling of Sialic Acids: A Comparative Study. (27th April 2017) - Dold, Jeremias E. G. A.; Pfotzer, Jessica; Späte, Anne‐Katrin; Wittmann, Valentin
Abstract: Sialic acids play an important role in numerous cell adhesion processes, and sialylation levels are known to be altered under certain pathogenic conditions, such as cancer. Metabolic glycoengineering with mannosamine derivatives is a convenient way to introduce non‐natural chemical reporter groups into sialylated glycoconjugates, offering the opportunity to label sialic acids by using bioorthogonal ligation chemistry. The labeling intensity depends not only on the rate of the ligation reaction but also on the extent to which the natural sialic acids are replaced by the modified ones; that is, the incorporation efficiency. Here, we present a comparative study of eight mannosamine derivatives featuring terminal alkenes as chemical reporter groups that can be labeled by an inverse‐electron‐demand Diels–Alder (DAinv) reaction. The derivatives differed in chain length as well as the type of linkage (carbamates, amides, and a urea) that connects the terminal alkene to the sugar. As a general trend, increasing chain lengths resulted in higher DAinv reactivity and, at the same time, reduced incorporation efficiency. Carbamates were better accepted than amides with the same chain length; nevertheless, the latter resulted in more intense cell‐surface staining, visible by live‐cell fluorescence microscopy. A urea derivative was also shown to be accepted. Abstract : Lengths and linkers : N ‐Acylmannosamine derivatives were evaluated for metabolic glycoengineering suitability. Terminal alkenes served as chemical reporter groups for bioorthogonal ligation with an inverse‐electron‐demand Diels–Alder reaction. Overall labeling efficiency on cell surfaces is dependent on both metabolic acceptance of the carbohydrate and its reactivity in the ligation reaction.